IEEE GLOBECOM 2007-2007 IEEE Global Telecommunications Conference 2007
DOI: 10.1109/glocom.2007.130
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adaptive Frequency Hopping for Wireless Personal Area Networks in a Coexistence Environment

Abstract: In this paper, we present an enhanced adaptive frequency hopping (EAFH) mechanism for improving the performance of frequency hopping-based wireless personal area networks (WPANs) under frequency-static and frequency-dynamic interference. The proposed mechanism monitors the overall packet error rate (PER) of the system to determine the right number of channels to be excluded from the hopset. Then based on the PER of individual channel, it decides whether to exclude a certain channel or not. Finally, proper pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The first step in AFH is to define and evaluate the quality of hopping sequences. Packet error rate is widely used as the channel quality metric [51][52] [5]. The second step is that coexisting networks choose their hopping set in a distributed manner such that both interferences from external networks and mutual interference are minimized.…”
Section: A Classification Of Spectrum Sharing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step in AFH is to define and evaluate the quality of hopping sequences. Packet error rate is widely used as the channel quality metric [51][52] [5]. The second step is that coexisting networks choose their hopping set in a distributed manner such that both interferences from external networks and mutual interference are minimized.…”
Section: A Classification Of Spectrum Sharing Methodsmentioning
confidence: 99%
“…Furthermore, it is almost impossible to allocate more spectrum resources to specific wireless networks due to regulatory constraints. Hence, the spectrum scarcity problem becomes more pronounced in more and more RF systems, e.g., cellular networks [1], vehicular communication networks [2], wireless local area networks (WLANs) [3], radar systems [4] and wireless personal area networks (WPANs) [5]. However, it has been observed that the usage efficiency of large quantities of current spectrum resources is rather low due to fixed spectrum allocation policies.…”
Section: Introductionmentioning
confidence: 99%
“…By now, several works has been proposed that studied the adaptive channel hopping issue [8,9,10], but most of them focuses on the channel selecting method. In our previous work, we present an adaptive channel hopping mechanism that is used for industrial WSN with star-like topology.…”
Section: Related Backgroundmentioning
confidence: 99%
“…Different channel selecting methods were proposed in [9] and [10], but they all aimed at those wireless networks where the stations had plenty of computational resource, so they are unsuitable for wireless sensor network.…”
Section: G Channel Selecting Strategymentioning
confidence: 99%
“…Another approach for avoiding both FD and FS interference, called Enhanced Adaptive Frequency Hopping (EAFH), was presented in [7]. FD interference is mitigated by moving the channels between three channel groups (one-slot, multi-slot and excluded channels) based on how i PER relates to the mean PER value ( PER ).…”
Section: Related Workmentioning
confidence: 99%